Analisa Pengaruh Heat Treatment Nilai Uji Kekerasan Mata Bajak Pada Mesin Pembajak Sawah Roda Satu - Yanto, Dedi; Martianis, Erwen (INOVTEK - SERI MESIN, 2023)
This reseach was conducted to determine the effect of variations in oil and brine media and temperature variations on the Rockwell hardness of KS steel plate (low karbon) 6 mm in the heat treatment process.the heat treatment process is widely used to increase hardness and add carbon elements to steel that has a low hardness value and needs to be given special treatment to increase the hardness of the steel. In this study the oil and salt water media.in this study the heat treatment process was carried out with variations in temperature, namely 7500C, 8000C after reaching the desired temperature and then held for 10 minutes. Meanwhile, for the Rockwell hardness test, the highest hardness value at 8000C was found in the brine media with a hardness value of 64,3HRC